UTILITAS MEDIA SOSIAL DALAM PENINGKATAN LITERASI POLITIK MAHASISWA UNIVERSITAS SAINS DAN TEKNOLOGI JAYAPURA” - Bao, Bonefasius; Samosir, Putri Anastasya (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2021)
The development of information technology has penetrated in all joints of human life. Sosial media, which initially served only as a means of self-existence, now metamorphosed to influence a country's political climate. In the era of reform the development of the use of sosial media is very massive for the expansion of democracy. Not infrequently his presence makes democracy always present paradoxical. The purpose of this study is to find out the Utility of Sosial Media in Improving Political Literacy of Jayapura University of Science and Technology Students. As well as knowing how much sosial media provides Utility in Improving Student Political Literacy. This research uses a quantitative approach whose research procedures produce descriptive data in the form of numbers that are then spelled out with words that get a clear picture of the observed behavioral tendencies. The results showed that 24% of respondents had an interest and interest in listening and improving their literacy through sosial media. Most respondents expressed little interest in discussions about politics (76%). Listening to these results it can be concluded that the utility of sosial media in improving the political literacy of USTJ students is still lacking. The importance of political education for students is a preference to help and provide a basic understanding to understand the dynamics of government politics in local and global contexts.